Type-I ELM mitigation by continuous lithium granule gravitational injection into the upper tungsten divertor in EAST. (13th May 2021) - Sun, Z.; Qian, Y.Z.; Maingi, R.; Wang, Y.F.; Wang, Y.M.; Nagy, A.; Tritz, K.; Lunsford, R.; Gilson, E.; Zuo, G.Z.; Xu, W.; Huang, M.; et al.
Abstract: Large edge-localized modes (ELMs) were mitigated by gravitational injection of lithium granules into the upper X -point region of the experimental advanced superconducting tokamak (EAST) device with tungsten plasma-facing components. The maximum ELM size was reduced by ∼70% in high β N H-mode plasmas. Large ELM stabilization was sustained for up to about 40 energy confinement times, with constant core radiated power and no evidence of high- Z or low- Z impurity accumulation. The lithium granules injection reduced the edge plasma pedestal density and temperature and their gradients, due to increased edge radiation and reduced recycling from the plasma-facing components. Ideal stability calculations using the ELITE code indicate that the stabilization of large ELMs correlates with improved stability of intermediate- n peeling-ballooning modes, due to reduced edge current resulting from the profile changes. The pedestal pressure reduction was partially offset by a core density increase, which resulted in a modest ∼7% drop in core stored energy and normalized energy confinement time. We surmise that the remnant small ELMs are triggered by the penetration of multiple Li granules just past the separatrix, similar to small ELMs triggered by deuterium pellet Futatani et al (2014 Nucl. Fusion 54 073008). This study extends previous ELM elimination with Li powder injection Maingi et al (2018 Nucl. Fusion 58 024003) in EAST because (1) use of small, dust-like powder and the related potential health hazards were eliminated, and (2) use of macroscopic granules should be more applicable to future devices, due to deeper penetration than dust particles, e.g. inside the separatrix with velocities ∼10 m s −1 in EAST.